Heat and Mass Transfer in a Micropolar Fluid with Newtonian Heating: An Exact Analysis - Abid, Hussanan; Mohd Zuki, Salleh; Khan, Ilyas; Razman, Mat Tahar (Springer, 2016)
Heat and mass transfer phenomenon in a micropolar fluid is analyzed. The fluid occupies the space over an infinite oscillating vertical plate with Newtonian heating. The plate executes cosine type of oscillations. Exact solutions are obtained using the Laplace transform technique. Expressions for velocity, microrotation, temperature and concentration are obtained. Graphs for velocity and microrotation are plotted for various embedded parameters and discussed.